Pelatihan Teater sebagai Alternatif Pendidikan Luar Sekolah pada Masa Pandemi Covid-19 di Rumah Belajar Bintang Kurenah, Kota Payakumbuh - Afrizal Harun; Meria Eliza; Syafira Salsabilla (Warta Pengabdian Andalas, 2021)
Community Service with the title "Theatre Training as an Alternative for Out-of-school Education during the Covid-19 Pandemic at the Rumah Belajar Bintang Kurenah, Payakumbuh City" is a program that involved the Bintang Kurenah Learning House as a partner in the theatre training. This theatre training for children and youth especially. There were three forms of training: basic theatre training (body exercises, vocal and taste exercises), folk games, and learning fairy tales and folklore. The methods used in this theatre training were arranged in several stages, such as; (1) providing primary material related to theatre theory, (2) conducting basic training on theatre, and (3) presentation of training results. The primary material about theatre provided participants with knowledge about the meaning and benefits of theatre in the world of art. Meanwhile, the basic theatre training focuses on exploring body (gestures), vocal processing, and feeling (emotions). The result of this training was that participants, both personally and collectively, make a simple repertoire in the form of pantomimes, read poetry, monologue, which was performed in front of parents and citizens in general.